The impact of servant leadership in nursing practice at the hospital: A literature review - Rosalia Yuli Purwanti; Ayun Sriatmi; Lucky Dwiantoro (Journal of Holistic Nursing Science, 2023)
Leadership style in nursing has influenced nurses and patients at hospitals. One of the styles suitable to put into practice is servant leadership, as there found valuable similarities in characteristics, such as being altruistic, serving, and healing. Servant leadership in nursing is closely related to the ability to influence nurse teams and hospital patients. This study aims to identify servant leadership's effects on nurses as a team and patients at hospitals. The research method used is the literature review. Database Sciencedirect, Proquest, Scopus, Clinicalkey, and SpringerLink are explored to search the desired articles by selecting keywords "Servant Leadership" AND "Patient" AND "Nurse." Papers selected as the data sources meet the following inclusion criteria, i.e., full-text articles published between 2012-2022 and discussing servant leadership in nursing. After studying four pieces, it is found that servant leadership acts on both nurses and patients. The effects of servant leadership on nurses are in innovative behavior, job performance, and nurse satisfaction. In contrast, its impact on the patients is in their satisfaction after using the health care services. Keywords: Leadership; nursing management; quality of care; nursing care; clinical nursing practice